2018
DOI: 10.1016/j.biopha.2018.09.057
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA THOR increases the stemness of gastric cancer cells via enhancing SOX9 mRNA stability

Abstract: This work aims to explore the roles and mechanisms of long non coding RNA (lncRNA) THOR in regulating the stemness of gastric cancer cells. RNA-sequencing combined with quantitative real-time PCR (qRT-PCR) indicated that lncRNA THOR level was significantly upregulated in gastric cancer tissues compared with that in normal adjacent tissues. Knockdown of THOR attenuated the stemnness of gastric cancer cells, evident by the decrease of stemness markers expression and capacity of cells spheroid formation. Further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 30 publications
2
53
0
Order By: Relevance
“…Metastasis-associated in colon cancer-1 antisense RNA (MACC1-AS1) could promote stemness of GC via fatty acid oxidation 43 . Knockdown of lncRNA testis-associated highly conserved oncogenic long non-coding RNA (THOR) inhibited the stemness of GC 44 . This study first revealed that xxx; FEZF1-AS1: FEZ family zinc finger 1 antisense RNA 1; H&E: hematoxylin and eosin; HMGA2: high-mobility group AT-hook 2; mRNA: messenger ribonucleic acid; Nanog: nanog homeobox; Oct: octamer-binding transcription factor; qRT-PCR: quantitative reverse transcription PCR; SOX: sex-determining region Y-Box transcription factor.…”
Section: Discussionmentioning
confidence: 99%
“…Metastasis-associated in colon cancer-1 antisense RNA (MACC1-AS1) could promote stemness of GC via fatty acid oxidation 43 . Knockdown of lncRNA testis-associated highly conserved oncogenic long non-coding RNA (THOR) inhibited the stemness of GC 44 . This study first revealed that xxx; FEZF1-AS1: FEZ family zinc finger 1 antisense RNA 1; H&E: hematoxylin and eosin; HMGA2: high-mobility group AT-hook 2; mRNA: messenger ribonucleic acid; Nanog: nanog homeobox; Oct: octamer-binding transcription factor; qRT-PCR: quantitative reverse transcription PCR; SOX: sex-determining region Y-Box transcription factor.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs could function by different pathways, such as lncRNAs serve as the protein co‐activators or co‐repressors, and thus the co‐regulators of mRNA and DNA . Recent studies have revealed the ceRNA roles of lncRNAs .…”
Section: Discussionmentioning
confidence: 99%
“…As described previously [28], in situ cell death detection kit (Roche, Penzberg, Upper Bavaria, Germany) was utilized to identify the apoptotic cells under the manufacturer's protocols. Nuclei were stained by DAPI.…”
Section: Terminal Deoxynucleotidyl Transferase Dutp Nick End Labelingmentioning
confidence: 99%